LIFE SURVIVAL STRATEGY MASYARAKAT MISKIN DESA SASUR KECAMATAN SAHU KABUPATEN HALMAHERA BARAT - Kuadang, Agnes; Kameo, Daniel D.; Therik, Wilson M.A. (Universitas Kristen Satya Wacana, 2019)
This study aims to describe and analyze the charcteristics of poverty that are faced by Sasur’s people in Sahu district, West Halmahera. The method used is qualitative descriptive with sample data from 188 families. The results showed that 90% of poor villagers are categorized as working-age and 100% of people are working in the informal sector. Survival strategies they use include: make loans to some traders, including coconut, nutmeg, cloves and cocoa traders, sell sopi and become laborers in the city. When it rains, they shift from rice farming activity to planting cassava and taro and this effort helps them survive.